English Camp Program to Improve Students’ English Skill at SMP IT Qurrata Ayyun Batusangkar - Delfita Yulianti; Neldawati Neldawati; Robiatul Aminah Hasibuan (KIPS Institute, 2025)
This study aims to describe the importance of implementing the English Camp program to improve the English language skills of students who participate in this program at SMP Islam Terpadu Qurrata Ayyun Batusangkar. The method used in this research is a descriptive method using a qualitative approach. The subjects of this research were the principal, English teachers, and students of SMP IT Qurrata Ayyun Batusangkar who participated in the English Camp program. The data collection techniques in this research are observation and interview techniques. Data analysis techniques were performed in stages, including data collection, reduction, presentation, and conclusion drawing or verification. The results showed the importance of the English Camp program in improving students' English skills, as seen from observations and interviews with research subjects. Document data on English Camp program activities supported the results of this study. From the results of this study, researchers also found that the English Camp program was used as a superior program at SMP IT Qurrata Ayyun Batusangkar because it improved students' English skills.